Design of a Web-based Traffic Accident Information System Using the Extreme Programming Method - Ayun, Rizka Qurrota; Syahidin, Yuda; Yunengsih, Yuyun (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The rapid development of technology in this era has prompted various sectors to undergo digitalization, including hospitals. The primary objective of this research is to create a web-based traffic accident information system that will enhance the efficiency of processing and reporting traffic accident patient data. Data was collected through interviews, observations, and literature studies using a descriptive qualitative approach. The software development method employed is extreme programming. The system is built using the Laravel v10 framework with the PHP v8.1 programming language, complemented by MySQL v8 as its database. The results of the study at Hospital X indicate that traffic accident data reporting is still conducted manually using Microsoft Excel. This research aims to provide a reference for healthcare facilities, especially hospitals, to develop such a system. The information system is built and tested using black-box testing. Based on the functional aspects tested, the system operates effectively. It can be concluded that the system is suitable for use. Thus, medical record officers no longer need to sort emergency department patient data by admission date, diagnosis, and external cause, thereby facilitating the aggregation process and producing more comprehensive information.